2022
DOI: 10.3390/jcm12010156
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Clinically Significant Prostate Cancer in Patients with PIRADS Categories 3–5 Undergoing Magnetic Resonance Imaging-Ultrasound Fusion Biopsy of the Prostate

Abstract: Prostate biopsy is recommended in cases of positive magnetic resonance imaging (MRI), defined as Prostate Imaging Reporting and Data System (PIRADS) category ≥ 3. However, most men with positive MRIs will not be diagnosed with clinically significant prostate cancer (csPC). Our goal was to evaluate pre-biopsy characteristics that influence the probability of a csPC diagnosis in these patients. We retrospectively analyzed 740 consecutive men with a positive MRI and no prior PC diagnosis who underwent MRI-ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…suggested the following independent predictive factors for CSPC in patients with PI-RADS 4 and 5 lesions: i) PI-RADS category 5, ii) prostate volume <40 ml, iii) no history of prostate biopsy, iv) lesion located in the PZ or both TZ and PZ, and v) PSAD >0.35 ng/ml/ml (12). Moreover, Szempliński et al (10) demonstrated that older age and a large maximum ROI size were associated with an increased risk of CSPC diagnosis. In summary, older age, no history of biopsy, high PI-RADS scores, high PSAD, low prostate volumes, PCa located in the PZ, and a large ROI are among the key factors leading to the detection of CSPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested the following independent predictive factors for CSPC in patients with PI-RADS 4 and 5 lesions: i) PI-RADS category 5, ii) prostate volume <40 ml, iii) no history of prostate biopsy, iv) lesion located in the PZ or both TZ and PZ, and v) PSAD >0.35 ng/ml/ml (12). Moreover, Szempliński et al (10) demonstrated that older age and a large maximum ROI size were associated with an increased risk of CSPC diagnosis. In summary, older age, no history of biopsy, high PI-RADS scores, high PSAD, low prostate volumes, PCa located in the PZ, and a large ROI are among the key factors leading to the detection of CSPC.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, some patients with PI-RADS 4 or 5 lesions are targeted biopsy (TB)-negative (8). Moreover, only a few studies (9)(10)(11) have elucidated the factors leading to TB negativity among these patients.…”
mentioning
confidence: 99%
“…In a previous report, Hakozaki et al suggested the following independent predictive factors for CSPC in patients with PI-RADS 4 and 5 lesions: i) PI-RADS category 5, ii) prostate volume < 40 mL, iii) no history of prostate biopsy, iv) lesion located in the PZ or both the TZ and PZ, and v) PSAD > 0.35 ng/mL/mL[11]. Moreover, Szempliński, et al demonstrated that older age, no previous biopsy history, having a PSA level ≥ 10 ng/mL, a small prostate volume, a PI-RADS category > 3, a large maximum ROI size, and a lesion located in the PZ were associated with an increased risk of CSPC diagnosis[12]. In summary, no history of biopsy, high PI-RADS scores, high PSAD, low prostate volumes, PCa located in the PZ, and a large ROI are among the key factors leading to the detection of CSPC.Furthermore, to increase the CSPC detection rate, we evaluated TB-negative patients with PI-RADS 4 or 5 lesions and found that 20% and 21% of those with PI-RADS 4 and 5 lesions, respectively, were TB-negative.Apfelbeck et al showed that TB was negative in 25.6% (126/493) of patients with PI-RADS 4 lesions and 12.7% (45/355) of those with PI-RADS 5 lesions[13].…”
mentioning
confidence: 99%